2022
DOI: 10.1007/s11096-022-01387-7
|View full text |Cite
|
Sign up to set email alerts
|

The standards of practice for delivery of polypharmacy and chronic disease medication reviews by general practice clinical pharmacists: a consensus study

Abstract: Background General practice in the UK is experiencing a crisis. Greater multidisciplinary working is a potential solution. The new general practice contract in Scotland encourages this and includes a new pharmacotherapy service to be delivered by General Practice Clinical Pharmacists (GPCPs). Consensus is lacking for the standards of practice for delivery of pharmacotherapy medication reviews (which are polypharmacy and chronic medication reviews) as part of this service. Aim To identify and validate standards… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There is a need for a deprescribing competency framework to help define responsibilities against capabilities and skills. Work on this has already begun, for example a curricular framework for an interprofessional approach to deprescribing [ 76 ], standards of practice for polypharmacy and chronic disease medication reviews in general practice [ 77 ] have been developed, and a deprescribing competency framework in nursing for older people is also under development [ 78 ]. Using competency frameworks to allocate roles within the MDT team regarding deprescribing decisions could be beneficial however more research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for a deprescribing competency framework to help define responsibilities against capabilities and skills. Work on this has already begun, for example a curricular framework for an interprofessional approach to deprescribing [ 76 ], standards of practice for polypharmacy and chronic disease medication reviews in general practice [ 77 ] have been developed, and a deprescribing competency framework in nursing for older people is also under development [ 78 ]. Using competency frameworks to allocate roles within the MDT team regarding deprescribing decisions could be beneficial however more research is needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…4.1 Scientific nature of the pharmaceutical care mode for cancer pain patients in primary care based on the Delphi method As a mature and reliable method that has been widely applied in the field of health services, the Delphi method is often used in the formulation of models and standards (Boulkedid et al, 2011). On the basis of the Delphi method, Katie et al (Earle-Payne et al, 2022) identified 44 practice standards for general clinical pharmacists to provide multiple medications and chronic disease drug treatment reviews and proved that such standards were acceptable and effective. Therefore, in this study, we used the Delphi method to construct a set of pharmaceutical care modes that could be suitable for cancer pain patients at the primary healthcare level in China.…”
Section: Discussionmentioning
confidence: 99%
“…The research highlighted that from standards of practice [35] often lead to SV experiences among pharmacists. SVP additionally erodes self-esteem and willingness to accept responsibility for complex interventions, which can be a barrier to the implementation of advanced services like medication reviews [36].…”
Section: Relevance For Clinical Practicementioning
confidence: 99%